Dvokrpi ginko (Ginkgo biloba L.) in njegov les - Torelli, Niko (Les (Ljubljana), 1999)
Ginkgo biloba (maidenhair tree) is the sole survivor of a genus that has changed little for more than 150 million years and is the only member of the phylum Ginkgophyta (Eliving fossilĚ). Ginkgo is dioecious and gimnospermous, but cones are not produced. It looks very much like a dicot tree except that its leaves have dichotomous veins and it bears naked ovules. Its unique feature amongst the seed plants is that fertilization is achieved by motile sperm. Its coniferoid wood lacks vessels. Anatomically it is readily distinguished from conifers bysingle large cells in the axial parenchyma strands containing druses. Ginkgo lack the regulary close-fitting rectangular tracheids characteristically found in most conifers. The tracheids are slightly rounded consequently giving rise to intercellular spaces. Latewood tracheids are not thickened. The low-density wood is homogeneous, soft, light brown and has silky sheen. Heartwood is lacking. After wounding dark brown discoloured wood form.
Keywords: evolucija; ginko; raba; les; ksilotomija